Culture and traditional architecture of Mamasa in west Sulawesi, Indonesia - Raeny Tenriola Indrus, Mithen Lullulangi, Onesimus Sampebua (Opción, 2019)
This qualitative research aims to find out the process of building traditional Mamasa architecture. Data collected by observation, interviews, and documentation has been analyzed via descriptive qualitative analysis. The results show that the development process which is a cultural activity done by the ancestors of the Mamasa people in building a traditional house is: 1) Marreto (Logging in the forest), 2) Kesaro (Carrying wood from the forest), 3) Ma'pake'dek banua (Establishing a house), 4) Mambubung, (Ritual of completion of work to build a house) and 5) Melambe (Thanksgiving Party).